Signaling Responses to N Starvation: Focusing on Wheat and Filling the Putative Gaps With Findings Obtained in Other Plants. A Review - Kong, Lingan; Zhang, Yunxiu; Du, Wanying; Xia, Haiyong; Fan, Shoujin; Zhang, Bin (Frontiers in plant science, 2021)
Wheat is one of the most important food crops worldwide. In recent decades, fertilizers, especially nitrogen (N), have been increasingly utilized to maximize wheat productivity. However, a large proportion of N is not used by plants and is in fact lost into the environment and causes serious environmental pollution. Therefore, achieving a low N optimum via efficient physiological and biochemical processes in wheat grown under low-N conditions is highly important for agricultural sustainability. Although N stress-related N capture in wheat has become a heavily researched subject, how this plant adapts and responds to N starvation has not been fully elucidated. This review summarizes the current knowledge on the signaling mechanisms activated in wheat plants in response to N starvation. Furthermore, we filled the putative gaps on this subject with findings obtained in other plants, primarily rice, maize, and Arabidopsis . Phytohormones have been determined to play essential roles in sensing environmental N starvation and transducing this signal into an adjustment of N transporters and phenotypic adaptation. The critical roles played by protein kinases and critical kinases and phosphatases, such as MAPK and PP2C, as well as the multifaceted functions of transcription factors, such as NF-Y, MYB, DOF, and WRKY, in regulating the expression levels of their target genes (proteins) for low-N tolerance are also discussed. Optimization of root system architecture (RSA) via root branching and thinning, improvement of N acquisition and assimilation, and fine-tuned autophagy are pivotal strategies by which plants respond to N starvation. In light of these findings, we attempted to construct regulatory networks for RSA modification and N uptake, transport, assimilation, and remobilization.